Swamp Angel, Pottawatomie County - Haddock, Brandon (Kansas State University, The Chapman Center for Rural Studies, 2010)
The author theorizes the name of "Swamp Angel" and its possible settlement by its remaining un-incorporated houses, grain silo and railroad tracks located on the floodplain of the Kansas River.
Brandon Haddock, “Swamp Angel, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/21.
Keywords: Big Blue River; Manhattan; Pottawatomie County; Republican River; Swamp Angel; St. George